THE LINGUO-STYLISTIC ANALYSIS OF THE WORD 'HEART' IN ENGLISH LANGUAGE BASED ON THE NOVEL “PRIDE AND PREJUDICE” - Musoyeva Khayitgul (Western European Studies, 2025)
This article presents a linguo-stylistic analysis of the word “heart” as used in Jane Austen’s novel Pride and Prejudice. Focusing on metaphorical and idiomatic expressions involving “heart,” the study examines how this word functions stylistically in character development, emotional expression, and thematic framing. A combined cognitive stylistic and corpus-informed approach is applied: all instances of “heart” in the novel are identified and analyzed in context, and patterns in frequency and collocation are noted. The analysis reveals that “heart” serves as a rich stylistic device in Austen’s narrative. It conveys sincerity and emotional depth, often via conceptual metaphors (e.g. heart as seat of emotion), and it highlights character perspectives (such as the head-versus-heart conflict). By drawing on Conceptual Metaphor Theory (Lakoff & Johnson, 1980), cognitive stylistics, and corpus stylistics, the article demonstrates that references to “heart” play a key role in expressing authenticity of feeling, irony, and the tension between emotion and reason in Pride and Prejudice. Examples from the text are provided with interpretations, and relevant theoretical frameworks are referenced to situate the findings in scholarly context. The study thus offers insight into how a single lexical item – “heart” – operates on multiple stylistic levels to enrich literary meaning in Austen’s novel.
Keywords: linguo-stylistics; Jane Austen; “Pride and Prejudice”